ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS KERJA TENAGA EDUKATIF PADA PENDIDIKAN TINGGI SWASTA DI KOTA MAKASSAR - Arnida Arnida (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2010)
This study aims to find out how the influence of the main workload, income, job retention and further education to labor productivity Lecturer at private universities are in the city of Makassar. The study was conducted at four private colleges existing in the city of Makassar, among others Indonesian Muslim University, University of East Indonesia, STIEM-Bongaya and STMIK - Handayani later the population was all faculty positions remain the minimum functional expert assistant. The method of analysis used SEM analysis (Structural Equation Model) with sampling using proportional stratified sampling method. The results showed that the main workload factors, income, job retention, continuing education together very influential and significant productivity level educational personnel (Lecturer) at private colleges existing in the city of Makassar.